Characterization of the ash deposits along deep-cooling of the exhaust gas in coal-fired power plants. Issue 2 (April 2020) - Liang, Zhiyuan; Zhao, Qinxin
Abstract: Ash deposition and condensation of acid vapors under deep-cooling of exhaust gas in a 1000 MW ultra-supercritical power plant were investigated. X-ray diffraction, X-ray fluorescence and laser particle size analyzers were employed to characterize the components, elements and particle size distribution of deposits at different metal wall temperatures. The results show that the deposits formed at the metal wall temperatures of 40 °C–60 °C were much thicker than the deposits at 70 °C–90 °C from the perspectives of the morphology and thickness. Fluorides and chlorides were observed in deposits formed at the metal wall temperatures of 40 °C–60 °C. Thin deposits were composed of Al-Si oxides and simple sulfates when the metal wall temperatures were 70 °C–90 °C. The dew-point temperatures of water, HCl and HF vapors were around 40 °C, 60 °C, and 60 °C, respectively. Basic ferric, aluminum and calcium sulfates, which were acted as traps to absorb the condensate and fly ash. Hydration played an important role in the growth of deposits formed at the metal wall temperature of 40 °C–60 °C. Highlights: Ash deposition behavior during deep-cooling of exhaust gas was investigated. Thick deposits were found on at the metal wall temperatures of 40°C–60 °C. Hydration promoted the growth of thick deposits formed at the metal wall temperature of 40°C–60 °C. The metal wall temperature of heat-exchangers is recommended exceeding 60 °C.